Prevention of heat exhaustion: focus on wrestling - Allen, T. W. (International Journal of Wrestling Science, 2020)
Of the several sports in which competitors are grouped according to body weight (wrestling, judo, weightlifting, boxing) wrestling is the most popular. Not only is the number of participants greater in wrestling, but the number and frequency of matches is far greater during each season for wrestlers. Wrestlers often adopt dangerous weight loss practices at a young age (Gibbs, 2009). It has been estimated that outstanding wrestlers will "make weight" 20 to 30 times each season and will likely repeat this process 200 times during their careers. Medical researchers, sports medicine physicians, athletic trainers, coaches and parents have raised concerns about not only the immediate and short-term effects of repeated occurrences of making weight, but the possible long-term effects of repeated episodes of food and water deprivation.